QSAR AND DOCKING STUDIES OF APHORPHINE DERIVATIVES AS EFFICACIOUS PARTIAL ANTAGONISTS FOR PARKINSON'S DISEASE - VENKATESWARLU BOLISETTY,; NAGESWAR RAO.K,; MANAIAH.V, (International Journal of Pharma and Bio Sciences, 2014)
Parkinson’s disease is caused due to enhanced dopaminergic activity in the substantia nigra, a region of the midbrain. Dopamine Receptors are the main drugs used in the treatment of Parkinson’s disease. In this work, docking studies have been performed in order to understand the interaction between Aphorphine inhibitor and Dopamine Receptors (D2). An increase in the calculated binding affinities between inhibitor and D2, reflects the experimental inhibitory activity, expressed in terms of the half maximal inhibitory concentration (IC50), which is found to be in the range 0.0004 to 11.5 μm, for the inhibitors employed. The AM1 and PM3 semi-empirical methods have been used to estimate the predictive power of final QSAR equations. QSAR coupled with molecular docking studies indicated that, [6aR]-6, 10 dimethyl-5, 6, 6a, 7-tetrahydro-4H dibenzo [de, g] quin derivative of Aphorphine showed the highest percentage of concentration and can become a potential lead for treating Parkinson’s disease.